2017
DOI: 10.1038/s41598-017-09361-4
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab efficacy in cases of chronic spontaneous urticaria is not explained by the inhibition of sera activity in effector cells

Abstract: Omalizumab (OmAb) is a humanized anti-IgE antibody approved for the treatment of chronic spontaneous urticaria (CSU). OmAb’s mechanism of action is known to include actions on free IgE and on pre-bound IgE. However, OmAb is equally and rapidly effective against autoimmune and non-autoimmune urticaria where IgE involvement is not clear, suggesting the involvement of additional mechanisms of action. In this study, we sought to investigate the ability of OmAb to inhibit mast cell and basophil degranulation induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“… Weekly Itch Score Outcomes with 300 mg dosage of omalizumab [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. ( A ): Mean difference: −4.09 [95% CI: −4.76, −3.42]; Heterogeneity: Tau² = 0.47; Chi² = 79.48, df = 9 ( p < 0.00001); I² = 89%; Test for overall effect: Z = 11.95 ( p < 0.00001).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“… Weekly Itch Score Outcomes with 300 mg dosage of omalizumab [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. ( A ): Mean difference: −4.09 [95% CI: −4.76, −3.42]; Heterogeneity: Tau² = 0.47; Chi² = 79.48, df = 9 ( p < 0.00001); I² = 89%; Test for overall effect: Z = 11.95 ( p < 0.00001).…”
Section: Figurementioning
confidence: 99%
“… Weekly Wheal Score Outcomes with 300 mg dosage of omalizumab [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 26 ]. ( A ): Mean difference: −5.17 [95% CI: −6.90, −3.43]; Heterogeneity: Tau² = 4.97; Chi² = 87.78, df = 8 ( p < 0.00001); I² = 91%; Test for overall effect: Z = 5.82 ( p < 0.00001) ( B ): Standardized mean difference: −1.45 [95% CI: −2.20, −0.69]; Heterogeneity: Tau² = 1.23; Chi² = 191.84, df = 8 ( p < 0.00001); I² = 96%; Test for overall effect: Z = 3.77 ( p = 0.0002).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…However, controversial results exist in different studies. Serrano-Candelas et al (30), did not observe any effect of omalizumab in relation with the inhibition of degranulation of mast cells or basophils in chronic urticaria patients' serum either before or during treatment. In contrast, Rodriguez-Trabado et al (31), found a decrease in time in the basophil's activation in a patient treated with omalizumab.…”
Section: Discussionmentioning
confidence: 89%
“…Nine RCTs 14,[30][31][32][33][34][35]39,40 reported adverse events, nine RCTs 14,[30][31][32][33][34][35]39,40 reported the weekly itch severity score, eight studies [30][31][32][33][34][35]39,40 reported the weekly five severity score, nine RCTs 4,14,30,31,33,34,36,39,40 reported weekly urticaria activity scores, and six studies 31,32,34,35,39,40 mentioned the dermatology life quality index. Other characteristics of the included studies are presented in Table 1.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%